FORMATION OF THE GEOLOGY-GEOPHYSICAL BLOCK IN SYSTEM OF GEOLOGICAL MONITORING (ON AN EXAMPLE ZHOLTYE VODY TOWN) - PIHULEVSKYI, P.; TIAPKIN, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of geophysical researches of fault-block tectonics estimate stability of a territory to modern natural-technogenic processes in bowels of the Earth and also help to predict intensity and directions of anthropogenous "intervention" in the nature.